De l’usage postcolonial de l’archive. Quelques pistes de réflexion - Crystel Pinçonnat (Amnis)
As an introduction to the file « The Postcolonial Uses of the Archive » included in this issue of Amnis, this paper presents the various articles, which were gathered around the question, inserting them into a more global reflection. The purpose of the project is to highlight the various ways, in which archives are used by contemporary artists – writers primarily, but also filmmakers and visual artists – in a postcolonial perspective.